Integrated modelling of lithium transport and radiation under a liquid lithium divertor on EAST - Z.X. Wen; Z.H. Gao; B. Liu; Z. Zhou; Z.C. Lin; Y. Feng; S.Y. Dai (Nuclear Materials and Energy)
The edge transport and core accumulation of lithium (Li) impurity under a liquid Li divertor on EAST have been investigated by the EMC3-EIRENE and STRAHL codes, respectively. At the edge region, the Li density distribution and power dissipation derived from divertor targets have been simulated by EMC3-EIRENE modeling. At the core region, the ONETWO and TGYRO codes are used to calculate the Li transport coefficients for STRAHL modeling, which is implemented through the OMFIT framework. At the core–edge transition region (ΨN = 0.95 ∼ 1.02, ΨN is the normalized poloidal flux coordinate), the representative distribution of Li2+ ion density is used for the comparison between EMC3-EIRENE and STRAHL modellings, which can achieve a reasonable agreement between two codes. On this basis, the Li-ion core density and radiation distributions have been analyzed by STRAHL modeling, which indicates there exist two radiation peaks located at the magnetic axis and ΨN = 1.01. The impacts of Li radiation on H-L back transition have been studied by Martin’s threshold power scaling law (Martin et al 2008J Phys Conf Ser 123 012033). The core radiation of lithium has a limited impact on the operation regime of EAST. Even for the maximum lithium effective sputtering coefficient of 0.1 used in the current study, it is still insufficient to cause H-L back transition.